1994
DOI: 10.1002/ddr.430320306
|View full text |Cite
|
Sign up to set email alerts
|

In vitro phamacology of MK‐996, a new potent and selective angiotensin II (AT1) receptor antagonist

Abstract: pyridin-3-yl)methyl)(l,l'-biphenyl)-2-yl)sulfonyIbenzamide) interacted in a competitive manner with rabbit aortic angiotensin II (All) receptors as determined by Scatchard analysis of specific binding of ['251]-Sar'lle8-All. MK-936 also exhibited high affinity at All receptors in several tissues from different animal species (K, = 0.1-0.4 nM). In vitro functional assays utilizing All-induced aldosterone release in rat adrenal cortical cells demonstrated further that MK-996 acts as a competitive, high affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
41
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 19 publications
5
41
1
Order By: Relevance
“…16,17 The dose of losartan (1 nmol) injected into the RVLM has been shown in a previous study to block AT 1 receptors. 4 In view of the fact that L-158,809 has an affinity for AT 1 receptors in the brain and other tissues that is 10 to 100 times greater than that of losartan, 16,17 it is likely that microinjection of 1 nmol L-158,809, as used in the present study, also blocked these receptors. At the same time, microinjections of these doses of losartan or L-158,809 into the RVLM had no effect on the somatosympathoexcitatory reflex, which is known to be mediated by glutamate receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16,17 The dose of losartan (1 nmol) injected into the RVLM has been shown in a previous study to block AT 1 receptors. 4 In view of the fact that L-158,809 has an affinity for AT 1 receptors in the brain and other tissues that is 10 to 100 times greater than that of losartan, 16,17 it is likely that microinjection of 1 nmol L-158,809, as used in the present study, also blocked these receptors. At the same time, microinjections of these doses of losartan or L-158,809 into the RVLM had no effect on the somatosympathoexcitatory reflex, which is known to be mediated by glutamate receptors.…”
Section: Discussionmentioning
confidence: 99%
“…This conclusion is further strengthened by the fact that the 2 compounds have different chemical structures, and that their only known common pharmacological property is their antagonism of AT 1 receptors. 16,17 AT 1 receptors mediate the actions of Ang II; therefore, it follows that Ang II is likely to be the endogenous neurotransmitter to RVLM neurons mediating excitatory inputs originating from the PVN. Consistent with this, application of Ang II to single spinally projecting RVLM neurons in vitro elicits a depolarizing effect that is due to a reduction in resting K ϩ conductance, an effect that is blocked by losartan.…”
Section: Tagawa and Dampney Function Of At 1 Receptors On Rvlm Pressomentioning
confidence: 99%
“…To investigate roles of Ang II type 1 (AT 1 ) receptor, actin cytoskeleton, and Src family tyrosine kinases, we incubated podocytes (by Mundel) for 1 hour with the highly potent and selective AT 1 receptor antagonist L-158,809 26 (10 nmol/L; kind gift from Merck Sharp Dohme Research Laboratories, Rahway, NJ), jasplakinolide (JASP; 100 nmol/L; Molecular Probes Inc., Eugene, OR), which is a cell-permeable monocyclic peptide that binds and stabilizes F-actin, 27 or the highly potent selective inhibitor of Src kinases PP1 28 (1 mol/L; BIOMOL Research Laboratories Inc., Plymouth Meeting, PA), respectively, followed by Ang II (10 Ϫ7 mol/L) for 1 hour in the continued presence of drugs. JASP alone had no effects on the distribution of podocyte molecules (data not shown).…”
Section: Cell Culture and Incubationmentioning
confidence: 99%
“…Indeed, the affinity of L-158,809 for AT1 receptors is similar to that of angiotensin II itself (1). Moreover, a recent experimental study (2) has shown that L-158,809 attenuates early left ventricular remodeling during canine myocardial infarction.…”
mentioning
confidence: 90%
“…L-158,809 is a highly selective angiotensin II type 1 (AT 1 ) receptor antagonist whose affinity for AT 1 receptor has been shown to be greater than the existing angiotensin II receptor antagonists (1). Indeed, the affinity of L-158,809 for AT1 receptors is similar to that of angiotensin II itself (1).…”
mentioning
confidence: 99%